Flow‐controlled fluoroscopic angiography for the assessment of vascular integrity in bioengineered kidneys. Issue 10 (5th May 2020) - Cohen, Shahar; Soffer‐Hirschberg, Sarit; Partouche, Shirly; Hovav, Benny; Gurevich, Michael; Mezhybovsky, Vadym; Tennak, Vladimir; Eisner, Sigal; Nesher, Eviatar; Mor, Eytan; Atar, Eli
Abstract: Perfusion decellularization has been proposed as a promising method for generating nonimmunogenic organs from allogeneic or xenogeneic donors. Several imaging modalities have been used to assess vascular integrity in bioengineered organs with no consistency in the methodology used. Here, we studied the use of fluoroscopic angiography performed under controlled flow conditions for vascular integrity assessment in bioengineered kidneys. Porcine kidneys underwent ex vivo angiography before and after perfusion decellularization. Arterial and venous patencies were defined as visualization of contrast medium (CM) in distal capillaries and renal vein, respectively. Changes in vascular permeability were visualized and quantified. No differences in patency were detected in decellularized kidneys compared with native kidneys. However, focal parenchymal opacities and significant delay in CM clearance were detected in decellularized kidneys, indicating increased permeability. Biopsy‐induced leakage was visualized in both groups, with digital subtraction angiography revealing minimal CM leakage earlier than nonsubtracted fluoroscopy. In summary, quantitative assessment of vascular permeability should be coupled with patency when studying the effect of perfusion decellularization on kidney vasculature. Flow‐controlled angiography should be considered as the method of choice for vascular assessment in bioengineered kidneys. Adopting this methodology for organs premodified ex vivo under normothermic machine perfusion settings is also suggested.